Enhancing audit quality and reducing costs: the impact of AI in banking and financial services - Johri, Amar; Sayal, Anu; Chong, Kim Mee; Khoja, Maysoon; N, Chaithra; Jha, Janhvi; Tyagi, Neha (Frontiers in Artificial Intelligence, 2026)
IntroductionAuditing methods have been significantly influenced by the combination of automation with artificial intelligence (AI) and have, in part, changed the roles of auditors and the quality of audits. Sampling-based traditional auditing has several challenges with identifying anomalies or new risks in financial information environments that are becoming increasingly complex and more data-rich.MethodsIn this study, AI-based techniques (machine learning and natural language processing) will be applied to a number of the steps involved in auditing financial information. The predictive model will be applied to lead propensity analysis and business volume forecasting, allowing the examination of both structured and unstructured data on financial statements and protecting the privacy of client data.ResultsA predictive model utilizing artificial intelligence (AI) was able to identify leads at an 87% rate of accuracy; forecasted business volume errors were less than 5%; and it explained nearly 94% of the variance between the AI model’s predictions and the actual loan disbursement amounts. Using AI for full dataset analysis instead of sample-based methods improved auditors’ ability to detect anomalies and allocate resources efficiently.DiscussionOverall, the research demonstrates that AI provides auditors the capability to evaluate all data for a company, automate routine tasks, and identify specific areas (high-risk/high-value) that may require further review compared to other auditing methods. The new methodology also allows for early identification of potential risks and improves the overall efficiency of audits without compromising the protection of the companies’ data.